PEMILIHAN PELAYANAN KESEHATAN DIRUANGAN RAWAT INAP RUMAH SAKIT PRIMA PEKANBARU - Rita Afni (Ensiklopedia of Journal, 2019)
Good health services are services that can be rece ived by the community and are reasonable in nature, which means it does not conflict with the beliefs, beliefs of the community, as well as the culture and customs that apply to the community. Conflicting and unnatural health services are not good health services. This study aims to determine what factors are associated with the selection of inpatient health care. This type of research is quantitative using a cross sectional design. The respondents were patients in the inpatient ward who were hospitalized for hari 2 days. The study sample was 73 patients using Purposive Sampling. The location of the study was conducted at Pekanbaru Prima Hospital in June 2019. The results showed that there was a relationship between the selection of health services in the inpatient room with service factors (p = 0.001, OR = 5.504), place factors (p = 0.001, OR = 5.197) and the price factor (p = 0.0001, OR = 8,182). It is hoped that the management of Prima Hospital will be able to conduct training for health workers to make health professionals professional and work according to the SOP and expected to hospital staff to be able to quickly respond to patients.